Pemadaman Api dengan Teknik Tradisional dan Modern di SMPN 2 Penajam Paser Utara (PPU) Desa Tengin Baru - Ade Irma Nur Ahirman; Ahmad Thariq Azis; Annisa Qotrunada; Cici Apriliya; Cindy Khofifah; Felita Audina Putri Arlen; Filemon Sihotang; Istia Vionalita; Muhammad Alif Aulidan; Suci Firdayanti (Abdimas Universal, 2024)
Fire is an event that no one ever expected, but can happen at any time and can happen to anyone. Many causes of fires that often occur around us are caused by several factors. For example, human, environmental, and technical factors. Human error is the most common cause of fires. This can occur due to negligence or carelessness, errors in the use of flammable tools or materials. Not only human negligence, but also factors that cause fires such as stoves, matches, leaking gas, burning garbage and so on. The socialization was carried out at SMPN 2 Penajam Paser Utara (PPU) which was attended by 56 students. It aims not only to increase participants' knowledge, but also to encourage them to spread the knowledge to friends at school and in the community. It is hoped that the younger generation can understand the causes of fires and how to overcome them with this knowledge, they are able to handle extinguishing independently when facing fires with light fire capacity, and can minimize the risk of fires around them.